2020
DOI: 10.1186/s12865-020-00351-2
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory role for CD72 expression on B cells and increased soluble CD72 in primary Sjogren’s syndrome

Abstract: Background: CD72, a co-receptor of B cell receptor (BCR), has been reported to have both positive and negative effects on B cell functions in several immunological diseases. The B cell plays an important role in the pathogenesis of primary Sjogren's syndrome (pSS). However, whether CD72 is involved in the process remains unknown. This study aimed to observe the possible role of CD72 in the pathogenesis of pSS. Results: A total of 60 cases who fulfilled the American-European Consensus Group (AECG) criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Markers for the activated memory B cells, B_4 (Figure 5D right), match those from a recent single-cell study of healthy individuals (King et al, 2021). The transitional B cell subtype (B_3) was annotated by marker genes, CD72 and TCL1A , identified from previous studies (Shen et al, 2020; Stewart et al, 2020). These findings are also consistent with our observation of TNFSF13B upregulation in these patients (identified in our LR analysis), as BAFF has been shown to enhance survival of these B cell subtypes (Hsu et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Markers for the activated memory B cells, B_4 (Figure 5D right), match those from a recent single-cell study of healthy individuals (King et al, 2021). The transitional B cell subtype (B_3) was annotated by marker genes, CD72 and TCL1A , identified from previous studies (Shen et al, 2020; Stewart et al, 2020). These findings are also consistent with our observation of TNFSF13B upregulation in these patients (identified in our LR analysis), as BAFF has been shown to enhance survival of these B cell subtypes (Hsu et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Our GSEA results also suggest that BTK is closely associated with the B-cell receptor signaling pathway. It was shown that BTK may be involved in the radioresistance process of NPC cells ( 27 ). This suggests to us that BTK may be a new key biomarker for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics that reduce the proliferation of B cells, including TGs (39) and HCQ (40), have been used to treat SS. Indeed, SS is considered an autoimmune disease associated with hyperactivity, a pathologic autoantibody response of B cells (41), and elevated levels of serum IgG (42). Therefore, the levels of immunoglobulins in peripheral blood are considered to be important indicators of SS activity (7).…”
Section: Discussionmentioning
confidence: 99%